Recurrent myocardial infarction as an unsolved problem of evidence-based medicine - S. Yu. Martsevich (Кардиоваскулярная терапия и профилактика, 2024)
The author brings out opinion on the prognostic role of recurrent myocardial infarction (MI) at the present time. For many years, recurrent MI was considered one of the most severe complications of primary MI. Differences in the official and scientific definition of recurrent MI are examined. These differences are the reason for the ambiguous assessment of the prevalence and prognostic role of recurrent MI. Analysis of the literature data makes it possible to conclude that recurrent MI is still accompanied by significantly higher mortality rates, both in the acute phase and in the long term, compared to primary MI. The main factors determining the unfavorable prognosis of life after recurrent MI are analyzed. It is noted that modern clinical guidelines do not contain data on the specifics of treatment for recurrent MI. Specific methods for the treatment of recurrent myocardial infarction should be developed.